The role of foreign language anxiety and task complexity on fluency in German learners of Dutch - Reitsma, Foekje; Ruigendijk, Esther (Dutch Journal of Applied Linguistics, 2024)
This study investigated which aspects of fluency are related to foreign language anxiety and proficiency, and how this interacts with task complexity during a non-exam situation. Sixty-one low-intermediate German learners of Dutch completed a foreign language anxiety questionnaire, a proficiency test and two speech production tasks. Correlational analyses showed that anxiety was negatively related to number of mid-clause pauses in a complex task. Proficiency was positively related to numerous speed and breakdown fluency measures in a simple task. Mixed-effects models demonstrated that proficiency predicted two fluency measures. Task type positively predicted speed fluency. Anxiety was not a significant predictor of any fluency measure, which may be related to participants’ relatively low anxiety level. This finding suggests that anxiety may not have a strong influence during speaking tasks that are not part of formal assessments.